Антропологія шлюбу: історико-правовий погляд - Бирилюк, О.М. (Держава і право, 2011)
Розкривається
основна
ідея та суть шлюбу
як добровільного
союзу
чоловіка
та
жінки на основі
християнського
віровчення.
За основу
взяте
вчення
Біблії, римське
право,
візантійські традиції
та особливості
руського
шлюбно-сімейного
права.
На основі
норм і практики
різних правових
систем
вказуються
церковна
та державна
форми
укладення
шлюбів і їх юридична
сила
в різних країнах. Раскрывается
основная
идея и сущность
брака
на основе
христианского
вероучения
как добровольного
союза
мужчины
и женщины.
За основу
взято
учение
Библии,
римское
право,
византийские
традиции
и особенности
русского
брачно-семейного
права.
На примере
норм и практики
разных
правовых
систем
указываются
церковная
и
государственная
формы
заключения
браков
и их юридическая
сила
в разных
странах. This article is an attempt to expose a basic idea and essence of marriage, as a voluntarily
union of man and woman on the basis of christian dogma. One took for basis studies of
Bible, Roman law, Byzantium traditions and features of the Russian matrimonial law On the
basis of norms and practice of the different legal frame the forms of issue of marriage are
specified: religious and civil marriage and their legal efficacy in different countries.